Preoperative nivolumab to evaluate pathological response in patients with stage I non-small cell lung cancer: a study protocol of phase II trial (POTENTIAL). Issue 3 (17th March 2021) - Kagimoto, Atsushi; Tsutani, Yasuhiro; Mimae, Takahiro; Miyata, Yoshihiro; Ikeda, Norihiko; Ito, Hiroyuki; Maniwa, Yoshimasa; Suzuki, Kenji; Tsuboi, Masahiro; Yoshimura, Kenichi; Umemoto, Seiji; Okada, Morihito
Abstract : Introduction: Recently, inhibition of programmed cell death 1 or its ligand has shown therapeutic effects on non-small cell lung cancer (NSCLC). However, the effectiveness of preoperative nivolumab monotherapy for stage I NSCLC remains unknown. The present study aimed to investigate the pathological response of preoperative treatment with nivolumab for clinically node negative but having a high risk of NSCLC recurrence. Methods and analysis: The Preoperative Nivolumab (Opdivo) to evaluate pathologic response in patients with stage I non-small cell lung cancer: a phase 2 trial (POTENTIAL) study is a multicentre phase II trial investigating efficacy of preoperative nivolumab for clinical stage I patients at high risk of recurrence. This study includes histologically or cytologically confirmed NSCLC patients with clinical N0 who were found on preoperative high-resolution CT to have a pure solid tumour without a ground-glass opacity component (clinical T1b, T1c or T2a) or a solid component measuring 2–4 cm in size (clinical T1c or T2a). Patients with epidermal growth factor receptor (EGFR) mutation (deletion of exon 19 or point mutation on exon21, L858R), anaplastic lymphoma kinase (ALK) translocation or c-ros oncogene 1 (ROS-1) translocation are excluded from this study. Nivolumab (240 mg/body) is administrated intravenously as preoperative therapy every 2 weeks for three cycles. Afterward, lobectomy and mediastinal lymph node dissection (ND 2a-1 or ND 2a-2) are performed. The primary endpoint is a pathological complete response in the resected specimens. The secondary endpoints are safety, response rates and major pathological response. The planed sample size is 50 patients. Patients have been enrolled since April 2019. Ethics and dissemination: This trial was approved by the Institutional Review Board of Hiroshima University Hospital and other participating institutions. This trial will help examine the efficacy of preoperative nivolumab therapy for clinical stage I NSCLC. Trial registration number: jRCT2061180016.